Treatment adherence and quality of life in colombian patients with lupus nephritis (2024)
Background: As with many other chronic diseases, systemic lupus erythematosus (SLE) and lupus nephritis (LN) have significant impacts on the health-related quality of life (HRQoL). Medication non-adherence is a significant challenge in the management of SLE, with consistently up to 75% of patients being non-adherent with their SLE medications. There is a need to assess the patient’s perspective using patient-reported outcomes (PROs) to better understand the current impact of LN on HRQoL and treatment adherence in our region. The aim of this study was to explore the relationship between HRQoL and treatment adherence in patients with LN from the Colombian Caribbean. Methods: A cross-sectional study was conducted from June to December 2022, including patients with biopsy-proven LN. HRQoL and treatment adherence were assessed using the Lupus Quality of Life (LupusQoL) and the Compliance Questionnaire in Rheumatology 19 (CQR19) instruments, respectively. Patients were categorized as adherent or nonadherent based on medication intake (defined as >80% correct dosage). Principal component analysis (PCA) was employed to identify principal components between adherent and non-adherent patients. Results: A total of 42 patients with LN were included. Of these, 38 (90%) were female, and the mean age was 31 ± 10 years. Proliferative class IV was the predominant histopathological profile (90%). Twenty-five (60%) patients were categorized as non-adherent. Across all LupusQoL domains, a comprehensive range of responses was observed. Pain, planning, and intimate relationships domains remained unaffected, while burden to others domain had the lowest score. Poorer planning score correlated with older age (r = 0.72; p < .05) and longer disease duration (r = 0.74; p < .05). SLEDAI-2 K correlated with the pain domain (r = 0.78; p < .05). Non-adherent patients exhibited significantly worse pain domain scores compared to adherent counterparts (p < .05). PCA showed strong interactions between planning and pain, as well as between physical health and body image domains. Conclusions: LupusQoL pain domain scores were significantly worse in non-adherent patients compared to adherent patients. Effective pain management could be a determinant in HRQoL and treatment adherence rates in our population.